2008
DOI: 10.1002/jbm.a.32145
|View full text |Cite
|
Sign up to set email alerts
|

The influence of Young's modulus of loaded implants on bone remodeling: An experimental and numerical study in the goat knee

Abstract: The aim of this study was to examine the influence of the Young's modulus of the implant material on the bone remodeling in a loaded condition. A combined animal experimental and computational study was set up. The animal experimental group comprised of 16 Saanen goats, each receiving one titanium implant (Young's modulus 110 GPa) and one high-density polyethylene (HDPE) implant (Young's modulus 1 GPa) in the left femoral condyle. Both types of implants received a titanium coating of 100 nm thickness. The impl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 46 publications
1
15
0
Order By: Relevance
“…Considering that other displacement values were very close and all values were below 1 µm, the biologic effect of this difference would be negligible under conventional loading and early loading. In addition, considering the Young's modulus of the implants tested, the outcome will also be negligible, as Stoppie et al [30] could not establish any correlation with relative micromotion and tissue response to loaded titanium-coated high-density polyethylene implants with low Young's modulus (1 GPa) or titanium implants. Thus, bone deformation findings around TiZr implants suggest that the overall stiffness of implant-bone complex may represent similar intraosseous implant stability behavior for titanium implants [11].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Considering that other displacement values were very close and all values were below 1 µm, the biologic effect of this difference would be negligible under conventional loading and early loading. In addition, considering the Young's modulus of the implants tested, the outcome will also be negligible, as Stoppie et al [30] could not establish any correlation with relative micromotion and tissue response to loaded titanium-coated high-density polyethylene implants with low Young's modulus (1 GPa) or titanium implants. Thus, bone deformation findings around TiZr implants suggest that the overall stiffness of implant-bone complex may represent similar intraosseous implant stability behavior for titanium implants [11].…”
Section: Discussionmentioning
confidence: 96%
“…While Rieger et al [27] recommended the use of tapered dental implants with a high Young's modulus, Hedia [17] reported that reduction in the Young's modulus of the implant could reduce the stresses in the cortical and trabecular bone by 16 and 15 %, respectively. In an animal and numerical validation study, Stoppie et al [30] found that a titanium-coated high-density polyethylene implant with low Young's modulus (1 GPa) had higher bone mass in the peri-implant zone after 6 months of loading than titanium implants, which was attributed to anabolic strains experienced in peri-implant bone. In the present study, the Young's modulus of the TiZr alloy implant (100 GPa) was slightly lower than the titanium implant (110 GPa), and this resulted in a stress field comparable to conventional titanium implants.…”
Section: Discussionmentioning
confidence: 97%
“…Stoppie et al. [23] used animal and finite element studies to research the responses of peri-implant tissue to different elastic implants. The results showed that greater bone formation, thicker trabeculae and a higher rate of bone-to-implant contact were detected in the more elastic implants compared with the stiffer implants.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, using metallic materials to repair bone defects cause the bone to be insufficiently loaded. This process, known as stress‐shielding, affects bone remodeling and healing, resulting in increased bone porosity or atrophy 27, 28. These disadvantages of current implant materials highlight the need for developing new materials, such as a composite of CNTs.…”
Section: Introductionmentioning
confidence: 99%